Digital transformation of spiritual care education: A scoping review protocol of technology-enhanced learning for nursing students and professionals - Peiyu Sun; Ya Shi; Guo Chen; Yun Chen; Guohua Fan; Yingying Cao (PLoS ONE, 2026)
Background Spiritual care is a fundamental yet often under-addressed component of holistic nursing, with nurses and nursing students globally reporting limited competency. Traditional education models face challenges in accessibility, scalability, and pedagogical depth. While digital technologies offer transformative potential for learning, the evidence regarding their application and effectiveness in spiritual care education remains fragmented and insufficiently synthesized. Objective This scoping review aims to systematically map the existing literature on the use of digital technologies in spiritual care education and training specifically for nurses and nursing students. Methods The review will be conducted following the Joanna Briggs Institute (JBI) methodology for scoping reviews and reported per the PRISMA-ScR guidelines. A comprehensive search will be performed across multiple databases (e.g., MEDLINE, CINAHL, PsycINFO, Web of Science, Scopus, CNKI, WanFang) from inception, supplemented by grey literature searches. Two independent reviewers will screen records, select studies, and extract data using a standardized form. We will include empirical studies focusing on digital interventions (e.g., online courses, mobile apps, virtual simulations) designed to develop spiritual care competency in the target population. Data will be analyzed using descriptive statistics and thematic analysis. Anticipated results The review will generate a comprehensive map and classification of existing digital spiritual education interventions, detailing their technological characteristics, pedagogical strategies, outcome measures, and implementation facilitators and barriers. It is expected to identify key evidence gaps and inconsistencies in the field. For example, we anticipate identifying virtual simulation, online modules, and mobile apps as the most common categories. Significance This will be the first scoping review to systematically consolidate evidence on digital spiritual education for nurses. The findings will provide a foundational resource to inform the future design, implementation, and evaluation of theoretically grounded, effective, and scalable digital training models, ultimately aiming to enhance spiritual care competence in nursing practice. Systematic review registration OSF registration number: https://doi.org/10.17605/OSF.IO/7VNHF .